The Extraordinary Nature of Barney's Drumming: A Complementary Study of Ordinary Noise Making in Chimpanzees - Dufour, Valérie; Pasquaretta, Cristian; Gayet, Pierre; Sterck, Elisabeth H. M. (Frontiers in Neuroscience, 2017)
In a previous study (Dufour et al. 2015) we reported the unusual characteristics of the drumming performance of a chimpanzee named Barney. His sound production, several sequences of repeated drumming on an up-turned plastic barrel, shared several features typical for human musical drumming: it was rhythmical, decontextualized, and well controlled by the chimpanzee. This type of performance raises questions about the origins of our musicality. Here we recorded spontaneously occurring events of sound production with objects in Barney’s colony. First we collected data on the duration of sound making. Here we examined whether (i) the context in which objects were used for sound production, (ii) the sex of the producer, (iii) the medium, and (iv) the technique used for sound production had any effect on the duration of sound making. Interestingly, duration of drumming differed across contexts, sex, and techniques. Then we filmed as many events as possible to increase our chances of recording sequences that would be musically similar to Barney’s performance in the original study. We filmed several long productions that were rhythmically interesting. However, none fully met the criteria of musical sound production, as previously reported for Barney.